The implementation of prophetic education in shaping students' Islamic character: A phenomenological study at MAS Plus Al-Ulum - Munawwarah, Raudhatul; Darlis, Ahmad (STAI Auliaurrasyidin Tembilahan, 2025)
Prophetic education plays a strategic role in shaping students' Islamic character by instilling noble values inspired by Prophet Muhammad (peace be upon him) and addressing contemporary moral challenges. This study analyzes the implementation and outcomes of prophetic education at MAS Plus Al-Ulum Medan using a qualitative descriptive approach with a phenomenological perspective. Data were collected through interviews, observations, and document analysis, involving the Head of the Madrasa, the Vice Head for Student Affairs, and the Akidah Akhlak teacher. Findings reveal three key pillars: (1) Transcendence, through Qur'anic memorization, congregational prayers, and religious activities to develop religiosity; (2) Humanization, via mau’izhah hasanah (good advice) and uswatun hasanah (exemplary conduct) to instill moral values; and (3) Liberation, teaching discipline and responsibility through sanctions like Qur'anic memorization and maintaining cleanliness. Prophetic education significantly supports Islamic character development and offers insights for holistic Islamic education models.